2015
DOI: 10.1099/jgv.0.000009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus NS5A: enigmatic but still promiscuous 10 years on!

Abstract: Since one of us co-authored a review on NS5A a decade ago, the hepatitis C virus (HCV) field has changed dramatically, primarily due to the advent of the JFH-1 cell culture infectious clone, which allowed the study of all aspects of the virus life cycle from entry to exit. This review will describe advances in our understanding of NS5A biology over the past decade, highlighting how the JFH-1 system has allowed us to determine that NS5A is essential not only in genome replication but also in the assembly of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
131
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 84 publications
0
131
0
1
Order By: Relevance
“…For more than 20 years since its first description by Kaneko et al in 1994 (31), genetic mutations that either ablate or mimic phosphorylation have been very instrumental in elucidating the functions of putative NS5A phosphorylation sites; however, direct observations or measurements of NS5A phosphorylation at specific sites have not been done until recently when the Harris group (18) produced the first phospho-specific antibody against Ser-222 phosphorylation and showed that Ser-222 phosphorylation corresponds to NS5A hyperphosphorylation. Recently, there are two major leaps that demonstrated critical roles of Ser-225 phosphorylation in the assembly of an active genome replication complex (32) as well as virion production (19); however, the functions of NS5A phosphorylation remain enigmatic and promiscuous (7). To dissect the functions of NS5A phosphorylation, we employed LC-MS/MSbased phosphoproteomics in the HCV (J6/JFH-1, genotype 2a)-infected Huh7.5.1 cells (33) and identified three high confidence NS5A phosphorylation sites conserved in the LCS I region across major genotypes (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For more than 20 years since its first description by Kaneko et al in 1994 (31), genetic mutations that either ablate or mimic phosphorylation have been very instrumental in elucidating the functions of putative NS5A phosphorylation sites; however, direct observations or measurements of NS5A phosphorylation at specific sites have not been done until recently when the Harris group (18) produced the first phospho-specific antibody against Ser-222 phosphorylation and showed that Ser-222 phosphorylation corresponds to NS5A hyperphosphorylation. Recently, there are two major leaps that demonstrated critical roles of Ser-225 phosphorylation in the assembly of an active genome replication complex (32) as well as virion production (19); however, the functions of NS5A phosphorylation remain enigmatic and promiscuous (7). To dissect the functions of NS5A phosphorylation, we employed LC-MS/MSbased phosphoproteomics in the HCV (J6/JFH-1, genotype 2a)-infected Huh7.5.1 cells (33) and identified three high confidence NS5A phosphorylation sites conserved in the LCS I region across major genotypes (Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an antibody against Ser-222 phosphorylation was developed (18), but the functions of Ser-222 phosphorylation remain unclear because alanine mutation at Ser-222 does not have an apparent phenotype (11,13,19). Moreover, whereas alanine mutation at Ser-225, Ser-229, Ser-232, and Ser-235 reduced HCV genotype 2a activity, the same mutations enhanced genotype 1b activity (11), adding another layer of complexity to the functions of NS5A phosphorylation (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that phosphorylation of NS5A and HCV replication are closely linked (7,15,44). To further explore whether vinexin ␤ influences the phosphorylation of NS5A, thereby regulating HCV replication, NS5A and vinexin ␤ were coexpressed in HEK 293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Since vinexin ␤ has no significant intrinsic enzyme activity (48), we speculate that another HF(s) may be involved in the regulation of NS5A phosphorylation via interaction with vinexin ␤. In addition, various cellular factors involved in viral replication have been identified through interaction with NS5A (44). Thus, we coexpressed GFP-tagged vinexin ␤ and red fluorescent protein (RFP)-fused binding partners of NS5A such as annexin A2, CK1␣, CK2␣, CyPA, FBXL2, FKBP8, hB-ind1, Hsp72, Pin1, PSTPIP2, VAP-A, and VAP-B in Huh7-Lunet cells (6,13,(49)(50)(51)(52)(53)(54)(55)(56)(57).…”
Section: Resultsmentioning
confidence: 99%